Tunable Berry curvature and transport crossover in topological Dirac semimetal KZnBi - Junseong Song (Nature Portfolio, 2021)
Abstract Topological Dirac semimetals have emerged as a platform to engineer Berry curvature with time-reversal symmetry breaking, which allows to access diverse quantum states in a single material system. It is of interest to realize such diversity in Dirac semimetals that provides insight on correlation between Berry curvature and quantum transport phenomena. Here, we report the transition between anomalous Hall and chiral fermion states in three-dimensional topological Dirac semimetal KZnBi, which is demonstrated by tuning the direction and flux of Berry curvature. Angle-dependent magneto-transport measurements show that both anomalous Hall resistance and positive magnetoresistance are maximized at 0° between net Berry curvature and rotational axis. We find that the unexpected crossover of anomalous Hall resistance and negative magnetoresistance suddenly occurs when the angle reaches to ~70°, indicating that Berry curvature strongly correlates with quantum transports of Dirac and chiral fermions. It would be interesting to tune Berry curvature within other quantum phases such as topological superconductivity.